MINLP synthesis of processes for the production of biogas from organic and animal waste - Drobež, R.; Novak Pintarič, Zorka; Pahor, B.; Kravanja, Zdravko (2009)
Summary: This paper describes a superstructure approach for the synthesis of biogas processes simultaneously with the selection of different process background alternatives. The superstructure consists of anaerobic fermentation under thermophilic or mesophilic conditions, including options for a rendering plant, with different organic and animal wastes from either existing or new plants, different water supplies, wastewater treatments and biogas usage options. An aggregated mathematical model with an economic objective function, formulated as a mixed-integer nonlinear programming (MINLP) problem, was developed. An industrial case study was applied to an existing large-scale meat company, in order to describe the mathematical model and illustrate the MINLP synthesis approach. The optimal solution indicates that significant benefit can be obtained if biogas processes are selected simultaneously with the selection of different process background alternatives thus yielding the optimal integration of biogas processes with their background
Bibliografija: 29 jed
Keywords: MINLP sinteza -- Bioplin -- Organski otpad -- Životinjski otpad